THE MOST COMMON COMPLICATIONS IN PATIENTS WHO HAVE HAD COVID-19 (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The impact of COVID-19 on the human body continues to be actively studied. However, despite numerous fatalities and millions of infection cases, many aspects of the disease remain unclear.